2021
DOI: 10.4997/jrcpe.2021.219
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of Cadaveric Dissection on First-Year Medical Students

Abstract: Background This cross-sectional study was carried out to ascertain if first-time cadaver dissections can cause acute stress disorder (ASD) in medical students, and if death anxiety and gender play a role in the development of these symptoms. Methods A total of 135 first-year medical students at the Services Institute of Medical Sciences and King Edward Medical University, Lahore, Pakistan, who had recently conducted their first ever cadaver dissection filled out three scales: the Impact of Event Scale-Revise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Dissection is characterized by some limitations in the human body donor program, and to ensure the autonomy of these potential cadaver donors, an adequate informed consent process must be carried out for ensuring that the bequest is a completely voluntary-based decision [ 11 ]. In addition, dissection on cadavers is considered, at first glance, a stressful experience that causes a wide range of symptoms among medical students, such as difficulty breathing, palpitations, and nausea [ 65 , 66 ]. These symptoms are associated with the strong odor caused by chemical substances used in the prevention of tissue decay and with the aim to kill potential pathogens [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dissection is characterized by some limitations in the human body donor program, and to ensure the autonomy of these potential cadaver donors, an adequate informed consent process must be carried out for ensuring that the bequest is a completely voluntary-based decision [ 11 ]. In addition, dissection on cadavers is considered, at first glance, a stressful experience that causes a wide range of symptoms among medical students, such as difficulty breathing, palpitations, and nausea [ 65 , 66 ]. These symptoms are associated with the strong odor caused by chemical substances used in the prevention of tissue decay and with the aim to kill potential pathogens [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of authors have reported the psychological effects of cadaver dissections, especially during initial experiences. Zubair, Waheed, and Shuja 15 had reported that the first-time exposure could cause acute stress disorder (ASD) in students. This was also similar to the report of Javadnia et al 16 In several instances, such psychological impacts were reported to have abated over time or with repeated exposure.…”
Section: Health Hazards That Dissector and Prosectors Are Exposed Tomentioning
confidence: 99%
“…We read with interest the article on the 'Psychological impact of cadaveric dissection on fi rst-year medical students', 1 which highlights that dissection can cause acute stress disorder. With traumatic emotional experiences of dissection increasingly being recognised, 2 we wanted to share our perspectives on performing dissection during medical school and offer some solutions that may reduce this psychological impact.…”
Section: Letters To the Editormentioning
confidence: 99%
“…As mentioned by the authors, students who experience acute stress disorder are at risk of developing more severe mental health issues, such as post-traumatic stress disorder. 1 In addition, students who fi nd these sessions more emotionally taxing may develop maladaptive coping strategies, such as denial and avoidance. Concerningly, this can have long-lasting consequences for their ability to care and empathise later on as doctors.…”
Section: Letters To the Editormentioning
confidence: 99%
See 1 more Smart Citation